Development of e-learning in improving student understanding of education management subjects based on cooperative learning (Lighthouse Publishing, 2023)
The research objective was to determine the effectiveness of learning in improving student learning outcomes in Education Management courses by developing a learning management system (LMS). The decline in educational administration student learning outcomes in courses is because the media used so far has not been optimal. This is the initial cause of low learning outcomes. Urgency, there is a gap between theory, reality and expectations, so, it is necessary to develop E-Learning to improve the learning process for Education Management and Educational Psychology Orientation courses. Research and Development (R&D) research method with the ADDIE strategy. The research subjects were the Educator Management course and the objects were 35 postgraduate educational administration students. Data collection techniques with product validation, instruments, pre-test and post-test. Engineering analysis, needs analysis, design, development, testing and evaluation. Data validation results, tests and assessment instruments are analyzed in stages until the product is declared valid, practical and effective. As a result, the score of the technology expert is 92.13, the learning model expert is 91.43, the peer assessment is 94.02, and all the assessments given are interpreted very well. In small trials, the mean post-test result was 88.40. Large group trial mean 90.83. The difference in the scores of students who use the product and those who do not use the product has a difference of 18.63. In conclusion, the developed product is capable of significantly increasing student learning outcomes in education management courses using E-Learning and is very effective.